(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
The aim of this article is to examine how weather phenomena affect the landscape, not only in terms of its visual or geomorphological appearance, but also by modifying the emotional disposition that the landscape evokes. By adopting an atmospheric perspective, I intend to demonstrate that each landscape possesses its own mood (Stimmung), closely linked to the atmospheric-climatic events that unfold within it. My hypothesis is that such phenomena, due to their pervasiveness on a sensory level, can produce a real metamorphosis of the landscape, which also extends to the affective qualities that the landscape ‘radiates’, and which therefore do not primarily depend on the perceiver. My analysis is structured into two parts. In the first part, a) I attempt to prove that meteorological and climatic atmospheres, due to their extra-psychic nature, cannot be explained in empathic-projective terms; and b) I propose understanding the landscape as an expressive whole whose ‘emotional physiognomy’ changes according to the atmospheres that pass through it. In the second part, I support my argument with a literary example to show how the fundamental emotional tone (Grundstimmung) of the landscape can change radically following the manifestation of a specific atmospheric phenomenon.